Dimensions of the psychological image of scenes of war horrors in Otto Dix’s productions - Barakat Abbas Saeed (Basrah Arts Journal, 2024)
he current research (the dimensions of the psychological image of scenes of the horrors of war in the productions of Auto Dix) included four chapters, the first included the research problem (what is the nature of the dimensions of the psychological image of the scenes of the horrors of war in the productions of Auto Dix?), the importance of the research, and the goal of the research represented by (identifying the dimensions of the image Psychological scenes of the horrors of war in Otto Dix's productions. Then the limits of the research are concerned with studying the works of the artist (Dix) that were produced in (Germany) within the year (1924) and defining the terms. The second chapter (theoretical framework) included two sections: the first: the image is psychological and philosophical. The second: (Otto Dix) and the shocking accumulation of war scenes. Then come the indicators of the theoretical framework. The third chapter (research procedures) included the framework of the research community, the (4) research sample, a technical model, the research tool, the research methodology, and analysis of the research sample models. The fourth chapter included the research results, conclusions, recommendations and proposals, and a number of results, including: 1. The reality of the psychological image of the artist (Dix) was influenced by the disturbing nightmare scenes that accompanied him during his life, resulting from his vision of scenes of murder and death. Then come the references, sources, and definitions included in the research.